Assessment of Association Between Venous Occlusion and Infection of Cardiac Implantable Electronic Devices. (March 2022) - Keyser, Andreas; Jungbauer, Carsten; Rennert, Janine; Linnemann, Birgit; Schmid, Christof; Schopka, Simon
The increasing number of patients treated with cardiac implantable electronic devices (CIEDs) and indications for complex pacing requires system revisions. Currently, data on venous patency in repeat CIED surgery involving lead (re)placement or extraction are largely missing. This study aimed to assess venous patency and risk factors in patients referred for repeat CIED lead surgery, emphasizing CIED infection. All consecutive patients requiring extraction, exchange, or additional placement of ≥1 CIED leads during reoperative procedures from January 2015 to March 2020 were evaluated in this retrospective study. Venography was performed in 475 patients. Venous patency could be assessed in 387 patients (81.5%). CIED infection with venous occlusion was detected in 74 patients compared with venous occlusion without infection in 14 patients ( P < .05). Concerning venous patency, novel oral anticoagulant medication appeared to be protective ( P < .05; odds ratio [OR]: .35). Infection of the CIED appeared to be strongly associated with venous occlusion (OR: 16.0). The sensitivity was only 64.15%, but the specificity was 96.1%. Number of leads involved and previous CIED procedures were not associated with venous occlusion. In conclusion, in patients with CIED, venous occlusion was strongly associated with device infection, but not with the number of leads or previous CIED procedures.